Dampak Kebijakan Suku Bunga Bank Indonesia Terhadap Return On Asset Bank Perkreditan Rakyat Di Provinsi Bali - Wardana, I Ketut; Setiawina, Nyoman Djinar; Budiasa, Gde Sudjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 05.NO.06. TAHUN 2016, 2016)
ABSTRACT Monetary policy that arranged by The Central Bank of  Indonesia have been influences to private bank in Indonesia, including rural bank that wer located at regional  provinces. The main goals of this research is to analyse the impact of interest rate monetary instrument (SBI) as monetary policy of Bank Indonesia, non performing loans (NPL), and loans to deposit ratio (LDR) to Laba berbasis Aset (Laba/Aset) (ROA) of rural bank (BPR).  This research have been developed econometric simultaneous equation model (SEM) called TSLS (Gujarati, 2004),  Pyndick and Rubinfeld (1994). The research have been found that ROA function have significantly using F statistics tes based on 5% criteria. Meanhile, the partial statistical test indicates only non performing loans is significant using 5% level of significance. According to analysis result, its can be concludes that the rising of SBI rate would be impact positively to LDR, hence at the next steps the LDR variabel woild be impact the ROA performance of rural bank. However, the rising of SBI rate could be improve to people saving ad reducing financial linkage of commercial bank. This research have been recoomended, firstly, is that bank of Indonesia supporting for financial assisment for rural bank as replacement of  financial linkage of commercial bank based on 14% rate  a year.     Secondly, that OJK have been controlled more transparent to commercial bank as the nearly competitor  colud be potentially lost of rural bank opportunity to operate in the same market segmentations.
Keywords: SBI, Laba berbasis Aset (Laba/Aset), loans to deposit ratio and non performing loans to rural bank.